Comparison of Diesel Particulate Matter Simulation Models and Ventilation Optimisation by Using Computational Fluid Dynamics - Chang, Ping (Curtin University, 2019)
I compared different computational fluid dynamics (CFD) numerical models for diesel particulate matter (DPM) simulation and validated the simulation data with the onsite measurement. Based on this, I built the optimum simulation model to reveal the DPM dispersion and distribution characteristics in underground mines. Meanwhile, I also used the CFD to optimize the auxiliary ventilation system to reduce the DPM pollution in development face.